KESELAMATAN DAN KESEHATAN KERJA SEBAGAI BAGIAN DARI KAMPUS DAN PEMBERDAYAANNYA - Saragih, Andreas M; Debataraja, Semangat Marudut Tua (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Darma Agung (LPPM_UDA), 2020)
Occupational Safety and Health at our Campus is all activities to guarantee and protect the safety and health of students and all employees through efforts to prevent accidents and diseases caused by the work of employees / lecturers and student recovery. The risks faced by employees and students in lectures for example are accidents in driving, falling off on campus due to playing or playing sports, lack of sleep due to activities, natural disasters, earthquakes, floods, fires, and so forth. The Need for Policy, Planning, Implementation and Operational, Inspection and corrective action, Management Review, and Continuous Improvement for the OSH program done on campus. OSH activities certainly involve all students, lecturers, and all staff, and employees on campus so that OSH is cultured and not just material in lectures on campus.